Impact of COVID-19 on the sexual function and self-esteem of young Brazilian undergraduate students - Ponsone, Giovana; Scudeller, Tânia Terezinha; Oliveira, Thais Passos de; Capozzoli, Bruna; Ferrari, Renata Bullio; Amaral, Maria Teresa Pace do; Zanetti, Miriam Raquel Diniz (ABCS Health Sciences, 2023)
Introduction: Satisfactory sexual function contributes considerably to women’s physical and mental health and is affected by several factors, including chronic stress. Since the beginning of the COVID-19 pandemic, these stressors have been intensified by fear of contamination and morbidity and mortality, deaths, and long-term social isolation. Objective: To evaluate the effect of the COVID-19 pandemic on the sexual function and self-esteem of young women attending university in Brazil and also investigate the importance of social isolation in these conditions. Methods: This longitudinal study included 90 students with active sexual life who answered questionnaires before (in person) and during (virtually) the pandemic. The instruments used were the Female Sexual Function Index (FSFI) and the Rosenberg Self-Esteem Scale. Results: Only 67 women answered all questionnaires sent during the pandemic and had a mean age of 22.9 (±2.99) years; most of them were eutrophic, healthy students and, had a fixed partner. The total FSFI score allowed us to classify women without sexual dysfunction and was not modified during the pandemic. On the other hand, the self-esteem found was slightly lower than that considered healthy and did not change during the pandemic. Women who maintained social distancing showed a statistically significant reduction in sexual function when compared to those who did not (p=0.003). Conclusion: The COVID-19 pandemic did not influence young women’s sexual function or self-esteem attending university in Brazil. However, the behavior of social isolation during the pandemic impaired the sexual function of these women.